2016
DOI: 10.1002/chem.201602264
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Non‐Innocent Cyclic (Alkyl)(Amino)Carbenes: Ligand Rearrangement, C−H and C−F Bond Activation

Abstract: A cyclic (alkyl)(amino)carbene (CAAC) was found to undergo unprecedented rearrangements and transformations of its core structure in the presence of Group 1 and 2 metals. Although the carbene was also found to be prone to intramolecular C-H activation, it was competent for intermolecular activation of a variety of sp-, sp(2) -, and sp(3) -hybridized C-H bonds. Double C-F activation of hexafluorobenzene was also observed in this work. These processes all hold relevance to the role of these carbenes in catalysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 119 publications
3
53
0
2
Order By: Relevance
“…NMR kinetic studies were undertaken to gain more information about the possible mechanism of initiation of 15 f . The rate of the reaction between 15 f and olefin 13 ([D 8 ]toluene, 60 °C) proved to be independent of the concentration of 13 (see the Supporting Information) and was in good agreement with the stability of 15 f in solution (which appears to be limited by the high lability and low stability of CAAC) 25. Experimental results suggest that a dissociative mechanism operates for 15 f (Scheme 3).…”
mentioning
confidence: 56%
See 3 more Smart Citations
“…NMR kinetic studies were undertaken to gain more information about the possible mechanism of initiation of 15 f . The rate of the reaction between 15 f and olefin 13 ([D 8 ]toluene, 60 °C) proved to be independent of the concentration of 13 (see the Supporting Information) and was in good agreement with the stability of 15 f in solution (which appears to be limited by the high lability and low stability of CAAC) 25. Experimental results suggest that a dissociative mechanism operates for 15 f (Scheme 3).…”
mentioning
confidence: 56%
“…[28] This results strongly support the classical mechanism in which active,14-electron species are formed via neutral ligand release and also prove that for 15 a dissociation of CAAC is the rate-limiting step.NMR kinetic studies were undertaken to gain more information about the possible mechanism of initiation of 15 f.T he rate of the reaction between 15 f and olefin 13 ([D 8 ]toluene,6 08 8C) proved to be independent of the concentration of 13 (see the Supporting Information) and was in good agreement with the stability of 15 f in solution (which appears to be limited by the high lability and low stability of CAAC). [25] Experimental results suggest that ad issociative mechanism operates for 15 f (Scheme 3). This,h owever,c annot be extrapolated to all complexes 15,a nd further theoretical and kinetic studies are needed to shed more light on the initiation mechanism of these (pre)catalysts.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 2 more Smart Citations
“…Ah andful of Group 1a nd Group 2C AACc omplexes have been isolated. [61] Even beryllium has been explored, which has been described by Dutton and Frenking as "the least investigated chemical element of the first octal row of the periodic table except inert neon." [62] Braunschweig et al [63] have shown that the reduction of a( CAAC)BeCl 2 complex in the presence of aC AACafforded the (CAAC) 2 Be adduct 1,inwhich the beryllium atom is in the formal zero oxidation state (Scheme 5).…”
Section: Caacs In Group 1a Nd Group 2element Chemistrymentioning
confidence: 99%